Implementasi Model PBL dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran PAI - Syafrizal, Syafrizal; Wirdati, Wirdati (ALSYS, 2024)
The purpose of this study was to determine the implementation of the Problem Based Learning learning model in improving students' critical thinking skills in Islamic Religious Education subjects. This study aims to examine: 1) Planning the PBL model in improving students' critical thinking skills in Islamic Religious Education subjects in class 5B SDN 05 Batu Bajanjang. 2) Implementation of the PBL model in improving students' critical thinking skills in Islamic Religious Education subjects in class 5B SDN 05 Batu Bajanjang. 3) eval_uation of the PBL model in improving students' critical thinking skills in Islamic Religious Education subjects in class 5B SDN 05 Batu Bajanjang. The method used in this study is qualitative with a case study type. The research implementation period was from July to August 2024. The research data obtained by the researcher through interviews with Islamic Religious Education teachers, 5 students of class 5B and the principal of SDN 05 Batu Bajanjang as well as observations made during classroom learning with the material Loving Orphans and also supported by documentation. After that, the data was analyzed and tested for validity using source and technique triangulation. The results of the study showed that: 1) The planning of the Problem Based Learning (PBL) model in Islamic Religious Education subjects in improving students' critical thinking skills in the material Loving Orphans in class 5B of SDN 05 Batu Bajanjang was guided by the RPP. 2) At the stage of implementing the Problem Based Learning (PBL) model, the teacher had fulfilled the PBL syntax, namely problem orientation towards students, organizing students, guiding individual and group investigations, developing and presenting work results, analyzing and eval_uating the problem-solving process. 3) eval_uation of the Problem Based Learning (PBL) model shows that Islamic Religious Education teachers do not use observation sheets to assess students' discussion results, teachers use written tests of essay practice questions where the form of questions given already meets the HOTS question criteria, so that it has been well tested regarding the increase in students' critical thinking skills during the PBL learning process in class 5B SDN 05 Batu Bajanjang.